2017
DOI: 10.17113/ftb.56.01.18.5422
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide Mitigation in fried Kochchi Kesel Chips using Free and Immobilized Fungal Asparaginase

Abstract: SUMMARYAcrylamide is formed when food products are fried at high temperature. Food researchers are constantly working on developing efficient methods for mitigating acrylamide in fried foods. In the present study, asparaginase from Aspergillus terreus was used for the pretreatment of kochchi kesel banana slices before frying to mitigate acrylamide formation during frying. The soaking and frying conditions were optimized using free and chitosan-immobilized asparaginase. The optimal soaking temperature and time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Study demonstrated that enzymatic pretreatment of foods with the enzyme asparaginase leads to significant reduction of acrylamide content, in addition to other treatment procedures (Agarwal & Sahu, 2014;Panel & Chain, 2015;Meghavarnam & Janakiraman, 2018). Different food products have been subjected to pretreatment with asparaginase, clearly demonstrating a reduction of acrylamide (Ravi & Gurunathan, 2018;Anese, 2016).…”
Section: -Asparaginase -Enzyme For Food Usementioning
confidence: 98%
“…Study demonstrated that enzymatic pretreatment of foods with the enzyme asparaginase leads to significant reduction of acrylamide content, in addition to other treatment procedures (Agarwal & Sahu, 2014;Panel & Chain, 2015;Meghavarnam & Janakiraman, 2018). Different food products have been subjected to pretreatment with asparaginase, clearly demonstrating a reduction of acrylamide (Ravi & Gurunathan, 2018;Anese, 2016).…”
Section: -Asparaginase -Enzyme For Food Usementioning
confidence: 98%
“…Kochchi kesel banana slices were soaked in 5 U/mL of free or immobilized enzyme suspension at 60 °C for 20 min and then fried at 180 °C for 25 min. The mitigation of acrylamide in fried kochchi kesel with treatment by chitosan-immobilized L-asparaginase decreased by approximately 49% compared to treatment with the free enzyme [ 126 ]. Immobilized L-asparaginase is more effective for acrylamide mitigation in food than the free enzyme because of its superior properties.…”
Section: Application Of Immobilized L-asparaginase In Foodmentioning
confidence: 99%
“…L-ASNase is also a promising agent for the food industry because it reduces the formation of toxic acrylamide. Acrylamide is formed as a result of the nonenzymatic interaction of sugars with L-asparagine when starchy foods are heated to 120 • C under low humidity conditions in the Maillard reaction [9][10][11]. Effects unrelated to the hydrolysis of asparagine or glutamine have been described for a number of L-ASNases [12][13][14].…”
Section: Introductionmentioning
confidence: 99%